Gambaran Kepadatan Tungau Debu Rumah di Rumah Siswa SDN 009 Petapahan Kecamatan Gunung Toar Kabupaten Kuantan Singingi Provinsi Riau - Lilly Haslinda; Irvi M Riadi (Jurnal Ilmu Kedokteran, 2023)
House dust mites (HDM) are essential in causing allergic diseases such as asthma and allergic rhinitis. The main factors affecting the growth and development of HDM are temperature, humidity and food availability. The study aimed to describe the HDM density at SDN 009 students' homes Petapahan, Kuantan Singingi Regency, Riau Province. This research is a descriptive study with a cross-sectional approach. House dust mites were identified using a light microscope directly in the parasitology laboratory; research samples were taken from two locations; bedrooms and living rooms. The results showed that the HDM density was higher in the bedroom than in the living room, with the HDM density in the bedroom being 12.5 mites/gram of dust and the HDM density in the living room being 10.37 mites/gram of dust. The total HDM density is 11.53 mites/gram of dust. HDM density is higher in bedrooms than in living rooms